LA TRADUCCIÓN EN LA ENSEÑANZA Y EN EL APRENDIZAJE DE LA LENGUA INGLESA: MATERIALES DE ESTUDIO - Enríquez Aranda, María Mercedes (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract Translation has been used as a procedure in second language teaching and learning from time immemorial. Its use has been restricted by the English language teaching and learning prevailing methods of different periods. Nowadays controversies arisen in this field are updated because of the development of translation studies as an autonomous academic discipline. Although interesting, there is scarce theoretical research on the topic. The most important studies are English and they are an essential starting point of later research. In practice, didactic handbooks used for English language and English literature teaching and addressed to advanced students illustrate the use of translation in this field. A careful exam of some sample cases of these two kinds of theoretical and practical materials shows the state of the art in the field.